And the Mountains Echoed - Hosseini, Khaled (New York Riverhead Books, 2014)
Presents a story inspired by human love, how people take care of one another, and how choices resonate through subsequent generations. Afghanistan, 1952. Abdullah and his sister Pari live with their father and step-mother in the small village of Shadbagh. Their father, Saboor, is constantly in search of work and they struggle together through poverty and brutal winters. To Adbullah, Pari, as beautiful and sweet-natured as the fairy for which she was named, is everything; there is an unparalleled bond between these two motherless siblings. What happens to them, and the large and small manners in which it echos through the lives of so many other people is an example of the moral complexity of life. In this multigenerational novel revolving around parents and children, brothers and sisters, cousins and caretakers, the author explores the many ways in which family members love, wound, betray, honor, and sacrifice for one another.
Keywords: Afghanistan -- Families -- Community life -- Interpersonal relations